2020
DOI: 10.7150/jca.46562
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA DSCAM-AS1 Facilitates Colorectal Cancer Cell Proliferation and Migration via miR-137/Notch1 Axis

Abstract: Growing evidences demonstrate that long noncoding RNAs (lncRNAs) participate in various cancers including colorectal cancer (CRC). In the current study, we found that the expression of DSCAM-AS1 in CRC tissues and cell lines was significantly upregulated, and was positively correlated with metastasis status and advanced stage of CRC. In addition, Kaplan-Meier assays also indicated that the expression of DSCAM-AS1 was correlated with poor prognosis in patients with CRC. Silence of DSCAM-AS1 inhibited proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Another study in colorectal cancer cells has shown the sponging effect of DSCAM-AS1 on miR-137 ( Xu et al, 2020 ). This miRNA has been found to suppress expression of Notch-1, a protein with essential roles in cell proliferation and epithelial-mesenchymal transition (EMT) ( Chu et al, 2019 ).…”
Section: Cell Line Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in colorectal cancer cells has shown the sponging effect of DSCAM-AS1 on miR-137 ( Xu et al, 2020 ). This miRNA has been found to suppress expression of Notch-1, a protein with essential roles in cell proliferation and epithelial-mesenchymal transition (EMT) ( Chu et al, 2019 ).…”
Section: Cell Line Experimentsmentioning
confidence: 99%
“…This miRNA has been found to suppress expression of Notch-1, a protein with essential roles in cell proliferation and epithelial-mesenchymal transition (EMT) ( Chu et al, 2019 ). Suppression of DSCAM-AS1 expression in colorectal cancer cells has resulted in down-regulation of Notch-1 ( Xu et al, 2020 ).…”
Section: Cell Line Experimentsmentioning
confidence: 99%
“…Bioinformatics analyses predicted the presence of a miR-137 seed region in the MSH2 3′UTR—with our in vitro results confirming MSH2 is targeted by miR-137. MiR-137, which is located on human chromosome 1p22, is reportedly present in neuronal cells [ 37 , 38 , 39 , 40 ], but is also found constitutively expressed in normal colonic epithelium [ 27 , 28 , 41 , 42 , 43 , 44 ], while low expression is found in adenomatous polyps and tumoral colorectal tissues [ 21 ]. Moreover, miR-137 locus is frequently hypermethylated in several tumor types, including colorectal, gastric, breast, head and neck squamous cell carcinoma, and colorectal adenomatous tissue [ 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA down syndrome cell adhesion molecule antisense RNA 1 (DSCAM-AS1) was originally identified as the most abundant Apo-ERα-regulated lncRNA (AER-lncRNA) in breast cancer [ 80 ]. Subsequent work ascribed an oncogenic role for DSCAM-AS1, with the expression in colorectal cancer associated with metastasis, advanced stage and poor overall survival [ 81 ], and in breast cancer linked with tumor progression and tamoxifen resistance [ 82 , 83 ]. Similarly, DSCAM-AS1 was proven highly expressed in osteosarcoma cell lines.…”
Section: Regulatory Network Of Lncrnas and Wnt Signaling Pathway In Osteosarcomamentioning
confidence: 99%